Odpowiedzi

2010-04-14T17:03:25+02:00
A) x + 7= 10
x=10-7
x=3
spr. 3+7=10
b)x-1=6
x=7
spr. 7-1=6
c)3x+6=9
3x=3/3
x=1
spr.3*1 +6=9
d)5= 3+ 7x
-7x=3-5
-7x= -2/-7
x=2/7
spr. 7*2/7 +3=5
e) ½x =11
x=22
spr. 1/2 * 22 =11
f) cztery dziewiąte x = ⅓
x= 1/3 *9/4
x=3/4
g) ⅓x + 1= 5
1/3x=4//1/3
x=12
h) 3x + 5=2x
x=-5
spr. -15 +5= -10
i) x= -2x
3x=1/3
x=1/3
j) 4 - x= 1,3
-x=-2,7
x=2,7
2 4 2
Najlepsza Odpowiedź!
2010-04-14T17:03:45+02:00
A) x + 7=10 /- 7
x = 3

Spr:
3+7 = 10

b) x - 1=6/ + 1
x = 7

Spr:
7-1 = 6

c) 3x+6=9 /-6
3x =3 / :3
x=1

Spr:
3*1 +6 =9
3+6=9

d) 5= 3+ 7x /-3
2 = 7x /:7
x= 2/7

Spr:
5 = 3 + 7* 2/7
5 =3 + 2

e) ½x =11 /*2
x = 22

Spr:
1/2 * 22 = 11

f) cztery dziewiąte x = ⅓ / * 9
4x = 3 / : 4
x = 3/4

Spr:
4/9 * 3/4 = 1/3

g) ⅓x + 1= 5 / -1
1/3x = 4 / *3
x = 12

Spr:
1/3 *12 = 4

h) 3x + 5=2x / -3x
5 =-x /* (-1)
-5 = x

Spr:
(3 * -5) + 5 = 2 * (-5)
-15 + 5 = -10

i) x= -2x /* (-1)
-x =2x /-2x
-3x = 0

Równanie sprzeczne.

j) 4 - x= 1,3 / - 4
-x = - 2,7 / * (-1)
x = 2,7

Spr:
4 - 2,7 = 1,3
2 5 2
2010-04-14T17:41:10+02:00
A) x + 7= 10
x=10-7
x=3
spr. 3+7=10

b)x-1=6
x=7
spr. 7-1=6

c)3x+6=9
3x=3/3
x=1

d)5= 3+ 7x
-7x=3-5
-7x= -2/-7
x=2/7

e) ½x =11
x=22
spr. 1/2 * 22 =11

f) cztery dziewiąte x = ⅓
x= 1/3 *9/4
x=3/4

g) ⅓x + 1= 5
1/3x=4//1/3
x=12
h) 3x + 5=2x
x=-5
spr. -15 +5= -10
i) x= -2x
3x=1/3
x=1/3
j) 4 - x= 1,3
-x=-2,7
x=2,7
1 5 1